Cultured Lung Fibroblasts from Ovalbumin-Challenged “Asthmatic” Mice Differ Functionally from Normal - Sugiura, Hisatoshi (American Thoracic Society, 2007)
Asthmatic airway remodeling is characterized by goblet cell hyperplasia, angiogenesis, smooth muscle hypertrophy, and subepithelial fibrosis. This study evaluated whether acquired changes in fibroblast phenotype could contribute to this remodeling. Airway and parenchymal fibroblasts from control or chronically ovalbumin (OVA)-sensitized and challenged “asthmatic” mice were assessed for several functions related to repair and remodeling ± exogenous transforming growth factor (TGF)-β. All OVA-challenged mouse fibroblasts demonstrated augmented gel contraction (P < 0.05) and chemotaxis (P < 0.05); increased TGF-β(1) (P < 0.05), fibronectin (P < 0.05), and vascular endothelial growth factor (P < 0.05) release; and expressed more α-smooth muscle actin (P < 0.05). TGF-β(1) stimulated both control and asthmatic fibroblasts, which retained all differences from control fibroblasts for all features(P < 0.05, all comparisons). Parenchymal fibroblasts proliferated more rapidly (P < 0.05), while airway fibroblasts proliferated similarly compared with control fibroblasts (P = 0.25). Thus, in this animal model, OVA-challenged mouse fibroblasts acquire a distinct phenotype that differs from control fibroblasts. The augmented profibrotic activity and mediator release of asthmatic fibroblasts could contribute to airway remodeling in asthma.